The problem of religious evil: Does belief in god cause evil? - Strickland, Lloyd (International journal for philosophy of religion, 2018)
Daniel Kodaj has recently developed a pro-atheistic argument that he calls "the problem of religious evil." This first premise of this argument is "belief in God causes evil." Although this idea that belief in God causes evil is widely accepted, certainly in the secular West, it is sufficiently problematic as to be unsuitable as a basis for an argument for atheism, as Kodaj seeks to use it. In this paper I shall highlight the problems inherent in it in three ways: by considering whether it is reasonable to say that "belief in God" causes evil; whether it is reasonable to say that belief in God "causes" evil; and whether it is reasonable to say that belief in God causes "evil." In each case I will argue that it is problematic to make such claims, and accordingly I will conclude that the premise "belief in God causes evil" is unacceptable as it stands, and consequently is unable to ground Kodaj's pro-atheistic argument.